Evidence-based capacity of natural cytochrome enzyme inhibitors to increase the effectivity of antineoplastic drugs - Laxmi Manthalkar; Ajazuddin; Sankha Bhattacharya (Discover Oncology, 2022)
Abstract Cytochrome (CYP) enzymes catalyze the metabolism of numerous exogenous and endogenous substrates in cancer therapy leading to significant drug interactions due to their metabolizing effect. CYP enzymes play an important role in the metabolism of essential anticancer medications. They are shown to be overexpressed in tumor cells at numerous locations in the body. This overexpression could be a result of lifestyle factors, presence of hereditary variants of CYP (Bio individuality) and multi-drug resistance. This finding has sparked an interest in using CYP inhibitors to lower their metabolizing activity as a result facilitating anti-cancer medications to have a therapeutic impact. As a result of the cytotoxic nature of synthetic enzyme inhibitors and the increased prevalence of herbal medication, natural CYP inhibitors have been identified as an excellent way to inhibit overexpression sighting their tendency to show less cytotoxicity, lesser adverse drug reactions and enhanced bioavailability. Nonetheless, their effect of lowering the hindrance caused in chemotherapy due to CYP enzymes remains unexploited to its fullest. It has been observed that there is a substantial decrease in first pass metabolism and increase in intestinal absorption of chemotherapeutic drugs like paclitaxel when administered along with flavonoids which help suppress certain specific cytochrome enzymes which play a role in paclitaxel metabolism. This review elaborates on the role and scope of phytochemicals in primary, secondary and tertiary care and how targeted prevention of cancer could be a breakthrough in the field of chemotherapy and oncology. This opens up a whole new area of research for delivery of these natural inhibitors along with anticancer drugs with the help of liposomes, micelles, nanoparticles, the usage of liquid biopsy analysis, artificial intelligence in medicine, risk assessment tools, multi-omics and multi-parametric analysis. Further, the site of action, mechanisms, metabolites involved, experimental models, doses and observations of two natural compounds, quercetin & thymoquinone, and two plant extracts, liquorice & garlic on CYP enzymes have been summarized. Graphical Abstract